Grade III of Blunt Thoracic Aortic Injury and Duodenal Perforation due to Multiple Trauma; Which Is Priority? A Case Report - Nasser Malekpour Alamdari; Iman Ansari; Hamed Askarpour; Maryam Abbasi (Clinical Case Reports)
ABSTRACT Perforation of the duodenum after trauma has a low incidence and its coincidence with BTAI is very rare. The clinical condition of the patient is very important for deciding the treatment priority. In this patient, considering the stable condition and degree of aorta injury, we chose TEVAR before laparotomy.